2013
DOI: 10.1371/journal.pone.0069622
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the NOC Gene Is Associated with Body Mass Index in Chinese Subjects

Abstract: Circadian clock genes are critical regulators of energy homeostasis and metabolism. However, whether variation in the circadian genes is associated with metabolic phenotypes in humans remains to be explored. In this study, we systemically genotyped 20 tag single nucleotide polymorphisms (SNPs) in 8 candidate genes involved in circadian clock, including CLOCK, BMAL1(ARNTL), PER1, PER2, CRY1, CRY2, CSNK1E,, and NOC(CCRN4L) in 1,510 non-diabetic Chinese subjects in Taipei and Yunlin populations in Taiwan. Their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Furthermore, an intronic SNP in CASS4 , a recently implicated gene for LOAD [9], has been suggested to affect the PAX3 binding motif [34]. The next most significant SNP (rs13116075; p =7.94E-06) was located in the CCRN4L gene on chromosome 4q31, which is expressed in the brain [35], and genetic variation in this gene has been shown previously to affect body mass index [36]. The third top SNP resides on chromosome 16p13 near PIGQ / RAB40C (rs2071979; p =8.17E-06).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an intronic SNP in CASS4 , a recently implicated gene for LOAD [9], has been suggested to affect the PAX3 binding motif [34]. The next most significant SNP (rs13116075; p =7.94E-06) was located in the CCRN4L gene on chromosome 4q31, which is expressed in the brain [35], and genetic variation in this gene has been shown previously to affect body mass index [36]. The third top SNP resides on chromosome 16p13 near PIGQ / RAB40C (rs2071979; p =8.17E-06).…”
Section: Discussionmentioning
confidence: 99%
“…[92][93][94] Insulin sensitivity is reduced in shift workers, accompanied by increased b-cell activity, suggesting the development of a prediabetic state. 100 In a further European study, the minor allele T of BMAL1-rs11022775 was associated with a higher odds ratio of T2DM than allele C in Asian populations, but the opposite association was observed in white European cohorts. In particular, CLOCK SNPs have been associated with obesity, 97 hyperglycaemia and a higher prevalence of T2DM in cross-sectional studies.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 87%
“…83 A recent report indicated a significant association between the combination of NOC (CCR4 carbon catabolite repression 4-like gene, CCRN4L) rs9684900 and BMAL1-rs2290035 with fasting blood glucose levels among 1510 nondiabetic Chinese subjects. 100 In a further European study, the minor allele T of BMAL1-rs11022775 was associated with a higher odds ratio of T2DM than allele C in Asian populations, but the opposite association was observed in white European cohorts. 101 In 346 pregnant Greek women, the frequency of the C allele of BMAL1-rs11022775 gene was significantly higher in patients with gestational diabetes mellitus than in controls.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 87%
“…Currently, insight into potential biological roles for human NOCT is limited to findings from genome-wide association studies (GWAS) and mRNA expression studies. One GWAS in Chinese men observed a correlation between the intronic tag SNP rs9684900 and body mass index [77]; however, it is not clear whether this SNP affects NOCT function, or whether this SNP or a closely-linked locus is the source of the association. NOCT mRNA abundance has been correlated with increased body mass index, suggesting a possible but unverified role in adipogenesis similar to that observed in mice [77].…”
Section: Noct Expression and Biological Functionsmentioning
confidence: 99%
“…One GWAS in Chinese men observed a correlation between the intronic tag SNP rs9684900 and body mass index [77]; however, it is not clear whether this SNP affects NOCT function, or whether this SNP or a closely-linked locus is the source of the association. NOCT mRNA abundance has been correlated with increased body mass index, suggesting a possible but unverified role in adipogenesis similar to that observed in mice [77]. Another GWAS study suggested a link between the intronic NOCT SNP rs3805213 and non-small cell lung cancer [78], while yet another study observed a correlation between NOCT expression and increased survival among small cell lung cancer patients [79].…”
Section: Noct Expression and Biological Functionsmentioning
confidence: 99%